Animal diversity - Hickman, Cleveland P. Jr; Roberts, Larry S.; Keen, Susan L.; Larson, Allan; Eisenhour, David J. (McGraw-Hill Education, 2015)
This text provides a concise introduction to the field of animal biology. After these introductory chapters, readers delve into the biology of all groups of animals. Chapter highlights include newly discovered features of animals as they relate to ecology, conservation biology, and value to human society.